Media Video Animasi 3D Sebagai Salah Satu Pembelajaran - Renovita Sarassati; Amrullah Amrullah; Ahmad Saipullah (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2018)
3D animation is the creation of moving images in 3 dimensional digital space. This is done by creating a frame that simulates each image. In 3D video animation learning is very much in the interest of today's society and the future, so the 3D media is very important in making animation, filmed with a virtual camera, and the output of the video which is already rendering or Realtime, if the goal is to create a game. 3D animations typically display at speeds in excess of 24 frames per second. The concept of 3D animation itself is a model that has the shape, volume, and space. 3D animation is at the heart of gaming and virtual reality, but usually 3D animation is also used in graphical presentations to add visual effects or movies.